IMPLEMENTASI METODE PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR SAMBRAMA WACANA PADA MASA PANDEMI COVID 19 (SISWA KELAS XI SMAN 1 BATURITI) - I Gede Sudiarta; I Nengah Juliawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Socio-cultural aspects of education in Balinese language subjects, which can improve students' abilities and skills, namely material about discourse sambrama. The Covid 19 pandemic has made the quality of education in Indonesia seem to be decreasing every day. The Covid-19 pandemic forces education actors to also pursue and develop themselves so as not to be left far behind. This obstacle causes a decrease in the ability of students to understand the values of discourse, both in the realm of theory and practice, this is obtained through the number of 34 students, but only 20 students complete and the rest are incomplete. This shows that classically only 58.82% of students completed. This teacher or educator must be able to design a lesson that can truly equip students with both theoretical and practical knowledge. One of the alternative answers to the above problems, the teacher can choose the Inquiry learning method with Classroom Action Research which strongly supports the program of improving the quality of learning in schools, which results in improving the quality of education whose reliability allows teachers to identify and formulate hypotheses convincingly, develop strategies which can be applied to situations in class XI SMAN 1 Baturiti.Keywords: Pandemic Covid 19, inquiry method, sambrama wacana, education.